Metabolic Status of Dairy Cows Grouped by Anabolic and Catabolic Indicators of Metabolic Stress in Early Lactation - Belić, Branislava; Cincović, Marko; Lakić, Ivana; Đoković, Radojica; Petrović, Milun; Ježek, Jožica; Starič, Jože (Acta Scientiae Veterinariae, 2018)
Background: Early lactation is period followed by changed metabolism in organism of the cow. This is the consequence of negativ energy balance, metabolic stress and milk production. Early lactation is characterised by high lipide catabolism (high NEFA) and low anabolic capacity (low insulin and IGF-I concentration). The aim of this study is to examine differences in metabolic adaptation of cows in early lactation (eight weeks after calving) in accordance to anabolic (insulin, IGF-I) and catabolic (NEFA) indicators in first week after calving. Materials, Methods & Results: The experiment included 50 Holstein-Friesian cows. Blood samples were collected in first, second, fourth and eight week after calving by venepunction of v.coccigea. Based on median value of indicator, cows were significantly (P < 0.001) classified in two groups: cows under metabolic stress (indicators of anabolism below the median Me-: indicators of catabolism above the medianMe+) and cows in control group (indicators of anabolism above the median Me+: indicators of catabolism under median Me-). Following criteria for comparison were given: based on classification of cows according to one indicator of metabolic load (insulinMe-:insulinMe+; IGF-IMe-:IGF-IMe+ and NEFAMe-:NEFA Me+); based on classification of cows according to combination of two indicators (insulinMe-+NEFAMe+: insulinMe++NEFAMe- and IGF-IMe-+NEFAMe+:IGF-IMe++NEFAMe-). Cows loaded with metabolic stress showed significan difference in metabolic adaptation in relation to control group (P < 0.05 or P < 0.01): higher values of STH, BHB (criteria were insulin, IGF-I, NEFA, insulin+NEFA, IGF-I+NEFA), higher values of bilirubin, AST, ALT, GGT, AP (criteria NEFA and IGF-I+NEFA) and MDA (criteria NEFA) and lower levels of glucose, total proteins, albumin (criteria IGF-I, NEFA, IGF-I+NEFA and body condition (criteria insulin, IGF-I, NEFA, insulin+ NEFA, IGF-I+ NEFA) were noted. Differences were expressed the most in first two weeks after calving. Differences in the body condition were the most notable later in weeks. Usage of NEFA indicator in first week after calving allows the most quality recognition of cows with metabolic parameters in extreme quartiles (ROC AUC= 0.87, P < 0.01) in first eight week of lactation. Discussion: Inverse relation betwen NEFA with insulin and IGF-I is consequence of next phisiological concept: plasma insulin and IGF-I decrease in same mannure after calvig and insulin aplication increase IGF-I; low insulin concentration leads cow to lipolysis and low IGF-I leads to STH resistance with increase concentration of STH and high lipolysis. Catabolism of adipose tissue and high NEFA concentration is most important for metabolic adaptation in periparturient period. Cows with insulin resistance, ketosis and fatty liver with many problems in metabolic adaptation showed high NEFA concentration. Atenuation of NEFA by niacin or anti-inflammatory drug decreases metabolic change due to high lipide mobilisation in early lactation. Low antepartal IGF-I showed significant effect on postpartum health, but our measuremens are in first week postpartum. In addition, increase catabolism of lipide viewed in NEFA value contributes to metabolic variation and adaptation in the first eight weeks of lactation much more than decrease of anabolic indicators such as insulin and IGF-I. The combination of the indicators does not lead to better recognition of cows with extreme metabolic change in relation to classification only to the value of NEFA.